Effects induced by living mulch on rhizosphere interactions in organic artichoke: The cultivar's adaptive strategy. Issue 3 (10th June 2016) - Trinchera, A.; Testani, E.; Ciaccia, C.; Campanelli, G.; Leteo, F.; Canali, S.
Abstract: The plant root apparatus and the surrounding micro-environment is strongly influenced by specific abiotic and biotic conditions which occur in the plant rhizosphere system. The hypothesis of the reported research was that, in an organically managed horticultural system, the use of living mulch (LM) promotes the arbuscular mycorrhizal fungi (AMF) colonization among neighboring roots, because of the coexistence of different plants roots in confined soil spaces. This effect determines nutrient uptake optimization, although roots belong to different plant species. In the reported 2-yr field experiment (2012–2013), two Italian artichoke cultivars [ Cynara cardunculus L. var. scolymus (L.), Jesino cv. and Mazzaferrata cv.] were intercropped with a LM mixture of plant species and compared with a no LM control. Every year, the effect of LM on artichoke root morphology and AMF colonization was evaluated by scanning electron microscopy, in order to assess abiotic and biotic rhizosphere interactions, as affected by artichoke cultivars. Also the artichoke yield, the soil available phosphorus (P) and rhizosphere P were determined. Results showed that the LM did not reduce yield of both the artichoke cultivars, when compared with the no LM ones. Furthermore, LM has: (i) induced structural changes in artichoke roots by proliferation of root hairs resulting in an increase of effective absorbing surface; (ii) promoted the rhizosphere mycorrhizal infection which improved P uptake. The modified rhizosphere interactions were found to be cultivar-dependent, being recorded only in Jesino artichoke.